2004
DOI: 10.1038/nn1339
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between decision making and performance monitoring within prefrontal cortex

Abstract: Our ability to judge the consequences of our actions is central to rational decision making. A large body of evidence implicates primate prefrontal regions in the regulation of this ability. It has proven extremely difficult, however, to separate functional areas in the frontal lobes. Using functional magnetic resonance imaging, we demonstrate complementary and reciprocal roles for the human orbitofrontal (OFC) and dorsal anterior cingulate cortices (ACd) in monitoring the outcome of behavior. Activation level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
282
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(319 citation statements)
references
References 50 publications
29
282
1
4
Order By: Relevance
“…Another difference with the current study is that in Breiter et al's study, the presented outcomes were not in any way contingent upon the participants' choices, or perceived by participants as such; instead, the participants were simply attending to the various stimulus displays. Importantly, recent research has demonstrated that the perception of action-outcome contingencies has a large impact on the (degree of) involvement of various brain areas in reward processing (Tricomi et al, 2004;Walton et al, 2004;Yeung et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Another difference with the current study is that in Breiter et al's study, the presented outcomes were not in any way contingent upon the participants' choices, or perceived by participants as such; instead, the participants were simply attending to the various stimulus displays. Importantly, recent research has demonstrated that the perception of action-outcome contingencies has a large impact on the (degree of) involvement of various brain areas in reward processing (Tricomi et al, 2004;Walton et al, 2004;Yeung et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral results are not immediately compatible with different arousal levels evoked by the High and Low Learning conditions. Recently, Walton et al (2004) have shown that the RCZa can be active not only on incorrect trials, but also on correct trials, provided that these trials convey behaviorally relevant information. In the current learning task, it is possible that the first correct trial associated with a specific mapping might have evoked ACC activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which the frontal lobes mediate response bias have only begun to be elucidated. Investigators have discussed the associations between frontal lobe function and response bias as part of the top-down processes (Swick & Knight, 1999) that are necessary to setting different criteria, such as monitoring (Shimamura, 2000;Walton et al, 2004) and controlling item retrieval (Buckner et al, 1996;Fletcher et al, 1998). There are several steps relying specifically on frontal lobe structures that must occur when individuals must decide whether presented stimuli have been presented before.…”
Section: Discussionmentioning
confidence: 99%
“…Response bias quantifies the tendency to either respond in a predominantly liberal (i.e., "yes") or conservative (i.e., "no") direction. Response bias has been linked to the frontal lobes, such that lesions to the frontal lobe will lead to a more liberal response set (Swick & Knight, 1999;Walton et al, 2004;Windmann et al, 2002). Importantly, response bias is theoretically independent of discriminability (Miller et al, 2001;Snodgrass & Corwin, 1988).…”
Section: Introductionmentioning
confidence: 99%